1991
DOI: 10.2307/2409695
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Benevolence in a Host-Parasite System

Abstract: A paradigm for the evolution of cooperation between parasites and their hosts argues that the mode of parasite transmission is critical to the long-term maintenance of cooperation. Cooperation is not expected to be maintained whenever the chief mode of transmission is horizontal: a parasite's progeny infect hosts unrelated to their parent's host. Cooperation is expected to be maintained if the chief mode of transmission is vertical: a parasite's progeny infect only the parent's host or descendants of that host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
133
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(140 citation statements)
references
References 4 publications
(4 reference statements)
3
133
1
Order By: Relevance
“…The theory underlying these expectations is similar to the patch model of foraging theory. In some experiments of this type, viruses and plasmids that were deleterious to their hosts became more benign and even beneficial to their hosts when the transmissibility of the agents or the availability of susceptible hosts was limited during evolution (Bouma & Lenski 1988;Bull et al 1991;Bull & Molineaux 1992;Lenski et al 1994), an outcome consistent with theory. In another experiment, however, a plasmid's horizontal and vertical transmission rates did not evolve as expected when host abundance was manipulated (Turner et al 1998).…”
Section: Introductionmentioning
confidence: 56%
“…The theory underlying these expectations is similar to the patch model of foraging theory. In some experiments of this type, viruses and plasmids that were deleterious to their hosts became more benign and even beneficial to their hosts when the transmissibility of the agents or the availability of susceptible hosts was limited during evolution (Bouma & Lenski 1988;Bull et al 1991;Bull & Molineaux 1992;Lenski et al 1994), an outcome consistent with theory. In another experiment, however, a plasmid's horizontal and vertical transmission rates did not evolve as expected when host abundance was manipulated (Turner et al 1998).…”
Section: Introductionmentioning
confidence: 56%
“…This result is consistent with a tight association between the fitness of the host and the fitness of its vertically transmitted parasite, suggesting that vertical transmission drives down parasite virulence as expected by the literature (Day & Proulx, 2004; Ewald, 1987; Lipsitch, Siller, & Nowak, 1996). Several experiments in different host–parasite systems have confirmed that vertically transmission usually selects for less virulent parasites (Bull, Molineux, & Rice, 1991; Magalon, Nidelet, Martin, & Kaltz, 2010; PagĂĄn, Montes, Milgroom, & GarcĂ­a‐Arenal, 2014; Stewart, Logsdon, & Kelley, 2005). This relationship is even suspected to be responsible for the general avirulence of mycoviruses, especially when high vc‐type diversity in host populations limits the occurrence of horizontal transmission (Brusini et al., 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Only one hybrid species, EpichloĂ« liyangensis , has ever been observed to produce stromata [40], so it appears that the hybrids are generally dependent on vertical transmission. Such a situation is expected to select for mutualism because the fitness of a vertically transmitted symbiont links positively to host fitness [41,42]. A common benefit conferred by epichloae to their hosts is the production of protective alkaloids that can deter, impair or even kill invertebrate and vertebrate herbivores [1,3,4,22,43,44,45,46,47,48,49,50,51,52,53].…”
Section: Discussionmentioning
confidence: 99%